On-court mechanical work measured using markerless motion capture is associated with acute fatigue in tennis - Emmerson, J.; Needham, L.; Evans, M.; Williams, S.; Colyer, S. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
Measurement of mechanical work with a markerless motion capture system was assessed for the application of training `load` monitoring. Four tennis players completed an on-court fatiguing protocol interspersed with sprint tests, with relationships between reduction in sprint velocity and internal and external mechanical work done tested. Repeated measures correlations for total and external mechanical work, and external mechanical work estimated from centre of mass proxies (pelvis and mid-hip) were comparable and ranged from -0.89 to -0.86. Whilst the calculated work done varied greatly between the methods (~42% for pelvis), all showed a strong relationship with fatigue and could provide insight into a player`s training `load`, despite the absolute values being inaccurate. This promising tool could be implemented for non-invasive, on-court training `load` monitoring in the field.